THE ASSOCIATION BETWEEN SMOKING DURING PREGNANCY AND HYPERTENSIVE DISORDERS OF PREGNANCY : A SYSTEMATIC REVIEW - Fahrozy, Akhmad (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Smoking is known to have an adverse effect on various health prognosis, and affects obstetric outcomes, such as stillbirth, preterm birth, and low birth weight during pregnancy. Conversely, the effect of smoking on hypertension during pregnancy is still unclear, with recent studies suggesting the effect differs by ethnicity. The aim: This study aims to show the association between smoking during pregnancy and hypertensive disorders of pregnancy. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 101 articles, whereas the results of our search on SagePub brought up 117 articles. The results of the search conducted for the last year of 2013 yielded a total 53 articles for PubMed and 70 articles for SagePub. The result from title screening, a total 11 articles for PubMed and 17 articles for SagePub. In the end, we compiled a total of 10 papers. We included five research that met the criteria. Conclusion: The association of maternal smoking during pregnancy with blood pressure and hypertension suggests that maternal smoking during pregnancy may have a long-term efect on children’s BP. Tis information should be transmitted to pregnant women and healthcare workers to decrease the risk of adverse cardio-metabolic outcomes.